Aneta Suchoń (ed.), The legal and economic aspects of associations and agricultural producers in selected countries of the world - Richli, Paul (Przegląd Prawa Rolnego, 2021)
Book review: Aneta Suchoń (ed.), The legal and economic aspects of associations and agricultural producers in selected countries of the world.